Analysis Study of Diagnostic Imaging Performance and Accuracy of Kidney Stone : A Comprehensive Systematic Review - Haekal Mahargias; Febrina Mayasari Gunawan (International Medical Journal Corp. Ltd, 2025)
Background: Kidney stones (nephrolithiasis/urolithiasis) are a prevalent urological condition caused by crystallization of minerals in the urinary tract. Their formation can lead to pain, hematuria, infections, and renal dysfunction if untreated. The increasing incidence of nephrolithiasis is linked to dietary habits, metabolic disorders, dehydration, and obesity. Imaging is crucial for early diagnosis and management, guiding treatment options such as conservative management, medical expulsive therapy, or surgical interventions. Objective: This systematic review aims to evaluate the diagnostic accuracy of various imaging modalities—ultrasound (US), non-contrast computed tomography (NCCT), contrast-enhanced CT, dual-energy CT (DECT), magnetic resonance imaging (MRI), and KUB X-ray—in detecting and characterizing kidney stones. Methods: The study follows PRISMA 2020 guidelines. Peer-reviewed studies published from 2015–2025 were identified through searches in PubMed, Embase, Cochrane Library, Web of Science, and Scopus. Inclusion criteria encompass studies assessing imaging performance in nephrolithiasis, with sensitivity, specificity, and predictive values as primary outcomes. Results: After screening, eight relevant studies were included. Ultrasonography, while radiation-free and cost-effective, has lower sensitivity than NCCT, the gold standard for kidney stone diagnosis due to its high accuracy. Dual-energy CT improves stone composition characterization, while MRI offers a radiation-free alternative but is less sensitive in detecting calcified stones. Conclusion: Imaging techniques vary in sensitivity and specificity for nephrolithiasis diagnosis. NCCT remains the most accurate, while US is preferred for radiation-sensitive populations. MRI may serve as a secondary tool where radiation exposure is a concern. Future advancements in imaging technology may further refine nephrolithiasis detection and characterization.